Assessment of the Antioxidant and Reactive Oxygen Species Scavenging Activity of Methanolic Extract of Caesalpinia crista Leaf. (18th June 2011) - Mandal, Sourav; Hazra, Bibhabasu; Sarkar, Rhitajit; Biswas, Santanu; Mandal, Nripendranath
Abstract : "Oxidative stress" is initiated by reactive oxygen species (ROS), which are responsible for majority of the diseases. However, antioxidants with ROS scavenging ability may have great relevance in the prevention of oxidative stress. The present study was undertaken, using a 70% methanolic extract of Caesalpinia crista leaves, to examine different in vitro tests in diversified fields including total antioxidant activity, scavenging activities for various ROS, iron chelating activity and phenolic and flavonoid contents. Total antioxidant activity was evaluated as trolox equivalent antioxidant capacity value of 0.546 ± 0.014. The extract was investigated for different ROS scavenging activities and IC50 values were found to be 0.44 ± 0.1 mg/ml, 24.9 ± 0.98 μ g/ml, 33.72 ± 0.85 μ g/ml, 61.13 ± 3.24 μ g/mL and 170.51 ± 4.68 μ g/mL for hydroxyl, superoxide, nitric oxide, singlet oxygen and hypochlorous acid, respectively; however, no significant results were obtained in scavenging of hydrogen peroxide and peroxynitrite anion. The extract was found to be a potent iron chelator with IC50 = 279.85 ± 4.72 μ g/mL. The plant extract (100 mg) yielded 50.23 ± 0.003 mg/mL gallic acid equivalent phenolic content and 106.83 ± 0.0003 mg/mL quercetin equivalent flavonoid content. In the in vivo experiments, the extract treatment showed significant increase in the level of superoxide dismutase, catalase, glutathione- S -transferase and reduced glutathione. In a word, it may be concluded that 70% methanol extract of C. crista leaves acts as an antioxidant and ROS scavenger; which may be due to the presence of phenolic and flavonoid compounds.